Bagaimana Anak Usia Dini Memahami Pendidikan Nilai-Nilai Agama? - Pujianti, Yuli; Rosa, Ade Tutty R.; Nuryati, Entin; Aminah, Siti (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
This study explored early childhood perceptions of religious values education at Kemala Bhayangkari 30 STIK Kindergarten. Using a quantitative approach with a survey method, this study involved 20 purposively selected children aged 4-6 years. Data was collected through direct observation to measure children's understanding of religious value concepts, such as honesty, kindness, and respect. The results showed that 40% of the children understood the value of honesty well, 35% understood the value of kindness, and 25% understood the value of respect. Children who engaged in interactive teaching with parental involvement showed higher understanding (85%) than children who only received lecture-based teaching (55%). In addition, support from the school environment also significantly influenced children's understanding, with a supportive environment resulting in a 90% comprehension rate. In comparison, a less supportive climate achieved only 55%. The study concludes that interactive teaching approaches, parental involvement, and support from the school environment are crucial in shaping children's understanding of religious values. The findings highlight the importance of improving teaching methods and cooperation between schools and parents in supporting the internalization of spiritual values in early childhood.